2021
DOI: 10.1159/000516389
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Gene Panel Approach in a Cohort of Patients with Incomplete Distal Renal Tubular Acidosis and Nephrolithiasis

Abstract: <b><i>Background:</i></b> Distal renal tubular acidosis (dRTA) is characterized by an impairment of urinary acidification resulting in metabolic acidosis, hypokalemia, and inappropriately elevated urine pH. If not treated, this chronic condition eventually leads to nephrocalcinosis, nephrolithiasis, impaired renal function, and bone demineralization. dRTA is a well-defined entity that can be diagnosed by genetic testing of 5 genes known to be disease-causative. Incomplete dRTA (idRTA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…The abnormality might be either acquired or genetic [ 28 ]. Evidence for the latter, however, was only found in 10% of idRTA patients with positive family history for stones in a recent genetic study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormality might be either acquired or genetic [ 28 ]. Evidence for the latter, however, was only found in 10% of idRTA patients with positive family history for stones in a recent genetic study [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For more equilibrated comparisons due to the strong female preponderance among idRTA patients (results), we formed 62 pairs of idiopathic calcium stone formers (ICSF) with and without idRTA, matched for gender, age, BMI and serum creatinine. Eleven idiopathic calcium stone formers (ICSF) with idRTA and positive family history for nephrolithiasis were also part of a recent genetic study [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…dRTA is characterized by an impairment of urinary acidification resulting in metabolic acidosis, hypokalemia, and inappropriately elevated urine pH. If not treated, this chronic condition eventually leads to nephrocalcinosis, nephrolithiasis and impaired renal function ( D'Ambrosio et al, 2021 ). Recently, a trans-ethnic GWAS in British and Japanese populations identified that rs578595, an intronic variant in WDR72 , was significantly associated with nephrolithiasis ( Howles et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…ПКА характеризуется нарушением экскреции нелетучих кислот почками при сохраненной скорости клубочковой фильтрации (СКФ) [14]. При ПКА в сыворотке крови прослеживается или нормальный анионный провал (то есть разница между содержанием катионов и анионов в плазме крови составляет 12 мэкв/л) или гиперхлоремический метаболический ацидоз, вызванный неспособностью почечных канальцев удерживать бикарбонат НСО3 − или секретировать ионы водорода Н + при нормальной или умеренно нарушенной функции почек [15].…”
Section: результатыunclassified
“…Авторы исследовали биоматериал 22 пациентов с семейным анамнезом МКБ и подтвержденной неполной формой дистального ПКА. В процессе работы были выполнены генетические тестирования с секвенированием 5 генов: SLC4A1 (OMIM 109270), ATP6V1B1 (OMIM 192132), ATP6V0A4 (OMIM 605239), FOXI1 (OMIM 601093) и WDR72 (OMIM 613214) и были обнаружены 2 гетерозиготные мутации в гене SLC4A1 у 2 исследуемых пациентов [14].…”
Section: клинические проявленияunclassified